EKSTRAK ETANOL DAUN BELUNTAS (Pluchea indica.L.) DAPAT MENGHAMBAT PERTUMBUHAN BAKTERI Streptococcus mutans - Maria Martina Nahak (Jurnal Kesehatan Gigi (Dental Health Journal), 2013)
Caries is a common disease of the teeth, caused by lactic acid produced by bacteria plaque through fermentation of substrate rich of sucrose and glucose. This bacteria plaque especially Streptococcus mutans produced acid from substrate and in a period of time change the oral cavity environment to become more acidity (pH 5.2-5.5) and at the time, demineralization process beginning and caries occurred. Indonesian Health Survey in the year 2004, found that caries prevalence in Indonesia achieved 90.05%. Basic Health Research in Indonesia in the year 2007, found that prevalence of tooth decay achieved 43,4%. According to this fact caries must be treated and prevented. Preventing caries must be done in many ways, one of this is using an antiseptic mouth rinsing from plant extract that is ethanol extract of beluntas leaves to prevent plaque formation and accumulation in tooth surface. The aim of this study is to know that ethanol extract of beluntas leaves can inhibit the growth of Streptococcus mutans. This is an experimental study with completely randomized with post test only control group design. Firstly, preparation of isolate of Streptococcus mutans and then preparation of ethanol extract of beluntas leaves in difference concentration, they are: 25%, 50%, 75% and 100%. To know an inhibitory effect of this extract against the growth of Streptococcus mutans was used diffusion disk method. Data was analyzed by One Way Anova, continuing by Least Significant Difference test. Qualitative analysis was used Chi-Square. This study found that there is a significant difference between control group and ethanol extract of beluntas leaves in varying concentration, they are 25%, 50%, 75% and 100% to inhibit the growth of Streptococcus mutans with p = 0.000. This study also found that ethanol extract with 25% of concentration shown the same inhibitory effect with chlorhexidine 0,12% as positive control and the inhibitory effect raising following the increasing of concentration of extract. Chi-Square analysis shown that there is a significant correlation between an inhibitory effect with the increasing of concentration of extract with p = 0.000.The conclusion is Ethanol Extract of beluntas leaves in varying concentration, they are 25%, 50%, 75% and 100%, can inhibit the growth of Streptococcus mutans. An advanced study need to determine minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of this extract and also the benefits of this extract as antiseptic mouth rinsing.